2015
DOI: 10.1080/0267257x.2015.1122659
|View full text |Cite
|
Sign up to set email alerts
|

Does market orientation pay off without brand orientation? A study of small business entrepreneurs

Abstract: Market orientation and brand orientation are usually modeled as distinct antecedents of business performance, and the simultaneous performance effects of these orientations are empirically under-explored. Moreover, studies of market orientation and branding tend to focus on large corporations and the views of managers rather than the views of small business entrepreneurs. Addressing these research gaps, the current study explores market orientation and brand orientation by empirically testing their simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 78 publications
(115 reference statements)
5
56
1
1
Order By: Relevance
“…It has been argued that the size and age of a firm have a significant impact on its strategic orientations and performance outcomes (Hirvonen et al, 2013;Laukkanen et al, 2016;Petruzzelli et al, 2018). The RBV recognises that the availability and optimisation of strategic resources influence firm performance, while strategic resources are subject to the firm's age and size (Arend, 2014;Halkos & Tzeremes, 2007;Thornhill & Amit, 2003;Tseng, Tansuhaj, Hallangan, & McCullough, 2007).…”
Section: Effects Of Firm Age and Firm Sizementioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that the size and age of a firm have a significant impact on its strategic orientations and performance outcomes (Hirvonen et al, 2013;Laukkanen et al, 2016;Petruzzelli et al, 2018). The RBV recognises that the availability and optimisation of strategic resources influence firm performance, while strategic resources are subject to the firm's age and size (Arend, 2014;Halkos & Tzeremes, 2007;Thornhill & Amit, 2003;Tseng, Tansuhaj, Hallangan, & McCullough, 2007).…”
Section: Effects Of Firm Age and Firm Sizementioning
confidence: 99%
“…Literature also suggests that the dynamics of how MO influences a firm's performance are subject to the attributes of the firm. Specifically, firm size and firm age are fundamental attributes that influence firm performance (Hirvonen, Laukkanen & Reijonen, 2013;Laukkanen, Tuominen, Reijonen & Hirvonen, 2016;Petruzzelli, Ardito & Savino, 2018). We postulate that identifying and understanding the influence of such attributes can provide a benchmark for practitioners to position themselves effectively and evaluate the feasibility and effectiveness of their strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that the sophistication of SME branding could be improved by adopting brand orientation (Wong and Merrilees ), placing importance on employee‐SME culture fit and communicating the essence of the brand to stakeholders (Rode and Vallaster ). When implemented together, market orientation and brand orientation, improve the performance of SMEs (Laukkanen et al ; Reijonen et al ). Some research suggests that low‐performing SMEs employ simplistic branding, while high‐performing ones utilize relatively sophisticated branding, similar to that found in large firms (Berthon, Ewing, and Napoli ).…”
Section: Sme Branding Literature Reviewmentioning
confidence: 99%
“…While Petkova, Rindova, and Gupta (2008) describe how PR is implemented by new ventures to create awareness and reputation among stakeholders, Bresciani and Eppler (2010) found that only few start-ups paid attention to their PR activities. Laukkanen et al (2016) show that brand orientation is a success factor for market orientation of entrepreneurs, but they do not take into account the role of PR for brand building.…”
Section: Adoption Of Pr Practices By Start-ups and Its Relevancementioning
confidence: 98%